Fixed Base Year vs. Chain Linking in National Accounts : Experience of Sub-Saharan African Countries - Dippelsman, Robert (IMF Working Papers; Working Paper ;, 2016)
There are two approaches for producing volume estimates of GDP, fixed base year and annual chaining. While most advanced economies have adopted the chain-linked approach in the past twenty years, some African countries are hesitant to do so, in part because of the computation and data requirements, and resource constraints. What difference does this make for the accuracy of the growth rates? From detailed data provided by three Sub-Saharan African countries we run simulations and conclude that the differences of GDP growth using the two approaches are small and do not behave in the consistent way found in advanced countries. We also show that weak deflation techniques and overly aggregated classifications used to derive volume measures can lead to large distortions. We conclude that improved deflation techniques and detailed classification should be addressed before adopting chain linking.